Koreografi Tari Ratok Maik Katurun Di Nagari Padang Laweh Kecamatan Koto VII Kabupaten Sijunjung - Izlatul Maulida; Herlinda Mansyur (SENDRATASIK UNP, 2021)
This study aims to reveal and describe the Choreography of Ratok Maik Katurun Dance in Padang Laweh Village, Koto VII District, Sijunjung Regency. Therefore, this study explores the problems related to the choreography contained in the Ratok Maik Katurun dance in Padang Laweh Village, Koto VII District, Sijunjung Regency. This research belongs to a qualitative research using descriptive methods. The main instrument of this research was the researcher itself and was assisted by supporting instruments such as writing tools and voice recorders. Types of data used were primary and secondary data. The data were collected through literature study, observation, interview, and documentation. The data analysis was conducted through data collection, data reduction, data presentation, and conclusion making. The results show that Ratok Maik Katurun Dance is a traditional dance which uses a choreographic approach and is created by raising the life of nature and the people of Padang Laweh village. Ratok Maik Katurun dance has a unique cultural value. It is dancing at the death of a leader in Padang Laweh village. Ratok Maik Katurun dance has two main aspects. The first one is the aspect of form including: motion (10 types of motion); simple floor designs such as straight and curved lines, top designs such as angular, medium, low, high, contrast and curved designs; group composition such as synchronously and balanced;female dancers aged 30-50 years; music using gondang boghek, talempong, and gong instruments; costumes worn is black baju kuruang basibah (Malay traditional clothes) and black songket (skirt); and properties in the form of shawls which are only worn in the oghak salendang movement. The second one is the aspect of content including: The idea, in Ratok Maik Katurun dance the idea isrelated to death and the atmosphere whichis sad. Music and dendang ratok used as accompaniment of the dance movements make the dance conveyed and complemented. Thus, it can be concluded that Ratok Maik Katurun Dance has choreographic aspects so that it can be researched using choreography knowledge.